Women and Miracle Stories : A Multidisciplinary Exploration - Korte, Anna (Numen Book Series, 2004)
This book contains a multidisciplinary collection of studies on women in miracle stories found in texts ranging from religious classics to contemporary literary fiction. Miracle stories are a genre of great importance for the study of women's religious inheritance and for the historical and cultural understanding of women as 'makers of faith'. Miracle stories are very generally speaking more open to popular religion and culture than, for instance, doctrinal and official ecclesiastical texts, and as such, they can be of special interest to the study of women's lives and religious aspirations. Remarkably, up till now this genre has not been looked at from this point of view. This book aims to open this field for further research by presenting case studies from diverse angles and disciplines. Some of the questions this book tries to answer are: What do miracle stories specifically tell us about women? Are there some (types of) miracles that are in particular related to (certain groups of) women? What do these stories tell us about women as performers and/or subjects of miracles? What can be said about the social function and religious meaning of miracles by specifically looking at the way certain groups of women are practising and experiencing miracles? By including research on miracle stories in contemporary fiction written by women this book also wants to acknowledge and research the disputed status of 'miracles' as well of 'women' in our present society which is moving from modernity to post-modernity. Please note that Women and Miracle Stories is previously published by Brill in hardback (ISBN 90 04 16681 8, still available).